Communication of Language The Impact of Journalism beyond 2003 (A Study in Attaakhi & Al-Sabaah Daily Newspapers) - Zainab Juma Al Saadi, Zainab Juma Al Saadi (ALBAHITH ALALAMI, 2013)
The methods used by the print media (press) is varied in conveying its messages and its orientations to the readers. But language takes the leading method among these methods, or a real competitor - so far - due to the characteristics and advantages of languages, including: ease, abbreviation, and development, etc.In the midst of such events, political tensions, and what they carry of the global developments, and among which was the most important the fall of the former Iraqi regime in the spring of 2003, the press had the greatest share, and a large portion on the level of monitoring, analyzing, and interpreting the various consequences of the event. The interpreting of the news varies according to the evolving political trends, and what it produced. In addition, this fall as a consequence, is a model of the robust totalitarian regimes. This, though, creates a an increasing in the successive event, and its successive consequences. Thus, this will achieve remarkable development and growing in the observing and documenting press.This research monitors the headlines in two Iraqi newspapers, namely: Attaakhi & Al-Sabaah Daily Newspapers, and the sample of the research was fixed in time period (approximately two months for Attaakhi Newspaper, and one month for Al-Sabaah Newspapers), as follows:Al-Taakhi Newspaper (Kurdish in Arabic version): starting with the No. (3982), the third session, May 10, 2003, corresponding to 9 Rabi al-Awwal 1424 AH to No. (4019), June 30, 2003, corresponding to 30 Rabi al-Thani 1424 AH.Al-Sabaah Newspaper (issued after the fall of the regime), No. (322), August 1, 2004, corresponding to 14 Jumada II 1425 AH, to issued No. (348), August 31, 2004, corresponding to 15 Rajab 1425 AH.The selection of the two newspapers comes at a time that exceeded the Year 2003. One of those newspapers represents a Kurdish nationalist viewpoint of the history of Iraq. The other one become, by the time goes, the quasi-official alternative to the former regime's press.The research was divided into two sections: the first one is theoretical dealing with the communication of language, and what is related to of links and other goals, highlighting the importance of the communication of language in the media. While the other one is applied section dealt with a study of the above-mentioned titles. The study concluded with a set of results hoping to be successful, this is done for the sake of Allah, praise be to Allah.